IMPLEMENTASI AKHLAK DALAM KOMUNIKASI MAHASISWA DI ERA MEDIA DIGITA - Feni Indriana; Sudanto; Abas Wismoyo Hermawan (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The digital media era has significantly transformed how university students communicate, interact, and express themselves. Unlimited access to information and a fast-paced communication culture present new challenges for students in maintaining moral and ethical values when engaging in digital spaces. This study aims to analyze the implementation of Islamic moral principles (akhlak) in student communication within the digital era by referring to previous research, particularly Salsabila (2023), which examines the alteration of ethical and moral values among university students due to technological advancement. This research employs a literature review method by examining journals, books, and relevant studies related to akhlak, Islamic communication, and students’ digital behavior. The findings indicate that although some students are able to uphold principles of politeness, honesty, and caution when using digital media, others experience moral degradation reflected in harsh expressions, unverified information sharing, and unethical digital interactions. The author argues that digital moral literacy must be strengthened through campus-based moral education, ethical communication training, and the habituation of Islamic values in students’ daily digital activities.